Signo e conversão : uma defesa de santo Agostinho das críticas de João de São Tomás - Souza, Edy Klévia Fraga de (2019)
In this thesis, the core of the discussion goes around the definition of “sign” given by Saint Augustine and widely criticized by Saint Thomas of Aquinas, and, consequently, by two philosophers of the second scholastic, viz., Domingo de Soto and João de Santo Tomás. In this way, first of all, I want to deliver a study on the theory of signs that can be found in three of Saint Augustine’s works, which are: Principia Dialecticae, De Magistro and Doctrina Christiana. Through these works I want to show that Augustine’s argumentative evolution on the signs and language ultimately aims at the process of man’s conversion to God. This will be clear in the approach of Augustine’s fourth work De Genesi ad Litteram. On this subject, Augustine and João de Santo Tomás are different in many aspects. If, on one hand, Saint Augustine has a theological motivation to accomplish a philosophy of language, on the other, João de Santo Tomás has epistemological and logical aims. The definition of “sign” given by João de Santo Tomás in Tratado dos Signos, aims at covering all types of signs, instrumental ones and formal ones. This thesis has still a chapter on the history of the second scholastic and its main contributions to the contemporary world. Given that João de Santo Tomás belongs to this part of the history of philosophy, this chapter aims at showing that the Augustine’s historic moment is completely different of João de Santo Tomás’ philosophy. More than one thousand years are between Augustine’s philosophy and João de Santo Tomás’ Philospphy.